(untitled) (Research, Society and Development, 2023)
The prognosis of people living with HIV obtained important progresses in the last two decades. The advent of Antiretroviral Therapy is a factor which provided the increase in life expectancy. However, this expectancy is still smaller than what is observed in the population without the HIV virus. One of the most important parameters to evaluate risks to the population’s health is the analysis of adhesion to the antiretroviral treatment. The objective of this study is outlining an epidemiological profile of a population living with HIV/Aids, relating to possible health risk factors. The research design which was adopted was of cross—sectional descriptive observational character. The convenience sample was 43 PVHIV, serviced at SAE/CTA from Ponta Grossa-PR. Only the variable “family income” presented significant association (p<0.05) with the evaluation of adhesion to the treatment, although analysis did not fulfill the expected count pre-requirement. The largest percentage of the individuals (41.86%) was diagnosed in the age group between 20 and 29 years old, the relationship status with highest predominance corresponds to singles (48.84%), the observed family income reaches in most cases up to a minimum salary (34.88%). A total of 25.58% declared as smokers, most predominantly among men.16.28% of the individuals reported arterial hypertension. We verified the general BMI average was 25.31 kg/m² (dp= 4), classified as overweight and with lipid profile above the recommended parameters. Thus it was concluded the need of implanting preventive and intervention actions aimed to reduce the risk factors in people living with HIV/Aids in antiretroviral therapy.